P176 COMPLICATED CROHN'S DISEASE IS ASSOCIATED WITH PERIANAL INVOLVEMENT, IBD-ASSOCIATED SEROLOGIES, AND POLYGENIC RISK SCORES DERIVED FROM IBD-ASSOCIATED VARIANTS. (18th January 2018) - Dube, Shishir; Gu, Phillip; Haritunians, Talin; Li, Dalin; McGovern, Dermot
Abstract: Background: In Crohn's disease (CD), disease severity is categorized by the Montreal classification. More complicated (stricturing and/or penetrating) disease is associated with poor quality of life. Our aim was to identify clinical, serological, and genetic factors associated with complicated CD. Methods: For each disease location, we performed case-control univariate analyses comparing stricturing (B2), stricturing and penetrating (B2/B3), or penetrating (B3) to non-stricturing/non-penetrating (B1) CD. Demographics and clinical features were obtained by chart review. ELISA was used to determine IBD-related serologies. Genotyping was performed using Illumina Immunochip array. Polygenic risk scores (PRS) were calculated using known IBD-associated variants weighted for effect sizes. Results: We included 1919 caucasian CD patients from a single center. Summary statistics for disease phenotype by disease location can be seen in Table 1. In small bowel (L1), colonic (L2), and ileocolonic (L3) disease, all three complicated disease phenotypes (B2, B2/B3, and B3) were associated with positive serology for ASCA IgA (OR 2.09–5.62, adj p < 2.84e-6). B2 (in L2 and L3) was associated with perianal involvement (OR 1.74–4.14, adj p < 0.01413). More complicated disease phenotype was associated with PRS for CD (OR 1.24–2.15, adj p < 0.0423) and B1 phenotype was associated with PRS for UC (Ulcerative Colitis) (OR 0.477–0.82, adj p < 0.0386). Conclusion: We have identified association of perianal involvement, ASCA IgA, and CD PRS to complicated disease behavior. In addition, we discovered a UC PRS association with B1 phenotype even in colonic disease. These findings can help identify patients at risk of developing more severe disease and help individualize management decisions.